2012
DOI: 10.3402/ijch.v71i0.18001
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency among northern Native Peoples: a real or apparent problem?

Abstract: Vitamin D deficiency seems to be common among northern Native peoples, notably Inuit and Amerindians. It has usually been attributed to: (1) higher latitudes that prevent vitamin D synthesis most of the year; (2) darker skin that blocks solar UVB; and (3) fewer dietary sources of vitamin D. Although vitamin D levels are clearly lower among northern Natives, it is less clear that these lower levels indicate a deficiency. The above factors predate European contact, yet pre-Columbian skeletons show few signs of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 48 publications
1
21
0
1
Order By: Relevance
“…Numerous studies have been performed to determine the prevalence of abnormal vitamin D status in children, but only a limited number of studies have been performed in non-Caucasian groups such as Argentinean Indians. Although vitamin D levels are clearly lower among Koya children, similar results were found in Natives from Canada (23). A recent study in Native North American children who lived in a reservation located at 43 • latitude, reported that 97% of them had a vitamin D concentration <30 ng/mL (10) Similarly, a vitamin D concentration <30 ng/mL was found in more than 95% of French Canadian children (11).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Numerous studies have been performed to determine the prevalence of abnormal vitamin D status in children, but only a limited number of studies have been performed in non-Caucasian groups such as Argentinean Indians. Although vitamin D levels are clearly lower among Koya children, similar results were found in Natives from Canada (23). A recent study in Native North American children who lived in a reservation located at 43 • latitude, reported that 97% of them had a vitamin D concentration <30 ng/mL (10) Similarly, a vitamin D concentration <30 ng/mL was found in more than 95% of French Canadian children (11).…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, Canadian Cree living in Manitoba have a significantly higher frequency of single nucleotide polymorphisms associated with a low expression of vitamin D receptors than a comparative Caucasian cohort (31). Thus, norms that were originally developed for European descendents may not be accurate models for vitamin D deficiency in American Indian populations (21,23).Our finding that all of the children in SAC had insufficient or deficient vitamin D levels implicates dark skin, high altitudes, or genetic backgrounds; it is unlikely that these findings reflect the catch-up growth of malnourished children because the exclusion of children who were underweight did not alter results.…”
Section: Discussionmentioning
confidence: 99%
“…It has been speculated that the frigid Arctic environment caused a selection of Inuit to adapt to a low calcium diet and low vitamin D (17,34). Most of the changes mentioned above are more recent and are thus not likely to counteract this hypothesized selection.…”
Section: Ethnicity and Vitamin D In Greenlandmentioning
confidence: 99%
“…The mean values of the 25 OHD3 content in adolescents (M = 37.9, SD = 12.2 nmol/L, n = 44) were significantly lower than in adults (M = 47.7, SD = 12.0 nmol/L, n = 52; p < 0.001). The mean value of 25 OHD3 in serum remains below 50 nmol/l in both age groups, usually depicted as the lower border of the recom mended level of the vitamin D content (Frost, 2012;Holick, 2007;Roth et al, 2005). The frequencies of FokI, BsmI, and ApaI alleles, as well as TaqαI and VDR genotypes, in the studied sam ple are shown in Table 2.…”
Section: Resultsmentioning
confidence: 96%
“…Undoubtedly, a significant role in this case is played by the traditional food content with its high vitamin D content in meat, fish, sea mammals, and reindeer fat (Kozlov, Ateeva, 2011;Björn, Wang, 2000). However, the possible role of anthropological (including that determined ethnically and ecologically) characteristics, possibly including the different tissue sensitivity to calciferol (Frost, 2012) and the population specifics of genetic determinants of the D vitamin exchange should be taken into consideration.…”
Section: Introductionmentioning
confidence: 99%